2018
DOI: 10.1105/tpc.17.00994
|View full text |Cite
|
Sign up to set email alerts
|

Photoexcited CRYPTOCHROME1 Interacts with Dephosphorylated BES1 to Regulate Brassinosteroid Signaling and Photomorphogenesis in Arabidopsis

Abstract: Cryptochromes (CRYs) are blue light photoreceptors that mediate a variety of light responses in plants and animals, including photomorphogenesis, flowering, and circadian rhythms. The signaling mechanism by which Arabidopsis thaliana cryptochromes CRY1 and CRY2 promote photomorphogenesis involves direct interactions with COP1, a RING motifcontaining E3 ubiquitin ligase, and its enhancer SPA1. Brassinosteroid (BR) is a key phytohormone involved in the repression of photomorphogenesis, and here, we show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 84 publications
(182 reference statements)
1
88
0
1
Order By: Relevance
“…As UVR8 can interact directly with several transcription factors (e.g., BES1, BIM1, WRKY36, MYB73, and MYB77) and thus mediate UV-B-regulated gene expression, UVR8 could also regulate the expression of the transcription factor gene HY5 to mediate UV-B-regulated gene expression. Liang et al (2018) and Wang et al (2018) established the molecular basis of cross-talk between UV-B light or blue light and brassinosteroid (BR) signaling. Nucleus-localized UVR8 interacts with BR-activated dephosphorylated BES1 and BIM1 in a UV-B-independent manner, while CRYs interact with dephosphorylated BES1 and BIM1 in a blue-light-dependent manner, repressing their DNAbinding activity and also the expression of elongation genes (Liang et al, 2018;Wang et al, 2018).…”
Section: Ia a 5 Ia A 1 9 H A T 2 S A U R 1 5 S A U R 6 3 G H 3 1 Ia mentioning
confidence: 99%
“…As UVR8 can interact directly with several transcription factors (e.g., BES1, BIM1, WRKY36, MYB73, and MYB77) and thus mediate UV-B-regulated gene expression, UVR8 could also regulate the expression of the transcription factor gene HY5 to mediate UV-B-regulated gene expression. Liang et al (2018) and Wang et al (2018) established the molecular basis of cross-talk between UV-B light or blue light and brassinosteroid (BR) signaling. Nucleus-localized UVR8 interacts with BR-activated dephosphorylated BES1 and BIM1 in a UV-B-independent manner, while CRYs interact with dephosphorylated BES1 and BIM1 in a blue-light-dependent manner, repressing their DNAbinding activity and also the expression of elongation genes (Liang et al, 2018;Wang et al, 2018).…”
Section: Ia a 5 Ia A 1 9 H A T 2 S A U R 1 5 S A U R 6 3 G H 3 1 Ia mentioning
confidence: 99%
“…A group of SINAT E3 ligases, on the contrary, are involved in degrading nonphosphorylated BES1 protein in the light [86]. In addition to light-controlled protein abundance of BES1 and BZR1, recent studies demonstrated that light negatively regulates the transcriptional activity of BES1 and BZR1 [88][89][90]92]. When illuminated by red and blue light, respectively, phytochrome B (phyB) and cryptochrome 1 (CRY1) interact specifically with nonphosphorylated BES1 and BZR1.…”
Section: Lightmentioning
confidence: 99%
“…When illuminated by red and blue light, respectively, phytochrome B (phyB) and cryptochrome 1 (CRY1) interact specifically with nonphosphorylated BES1 and BZR1. This light-dependent interaction leads to the inhibition of BES1 and BZR1 DNA-binding activity and ultimately the expression of their target genes [88][89][90]92]. Moreover, blue light-activated CRY1 also interacts with BIN2 and thus enhances the interaction between BIN2 and BZR1.…”
Section: Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenotypical experiments of seedlings defective for another class of blue light photoreceptors, called cryptochromes (cry), revealed that they modulate phototropism with a positive role in etiolated seedlings (Whippo and Hangarter, 2003; Ohgishi et al, 2004; Tsuchida-Mayama et al, 2010), and a potentially negative role in de-etiolated seedlings (Goyal et al, 2016). The Arabidopsis genome encodes two crys, cry1 and cry2, which coordinate blue light-mediated gene expression by the inactivation of the COP1/SPA E3 ligase complex (Holtkotte et al, 2017; Lau et al, 2019; Ponnu et al, 2019) or through the interaction with several transcription factors (Liu et al, 2008; Ma et al, 2016; Pedmale et al, 2016; Wang et al, 2018; Xu et al, 2018; He et al, 2019; Mao et al, 2020). Light-induced activation of cry1 and cry2 is controlled by BIC1 (Blue light Inhibitor of Cryptochrome 1) and BIC2 (Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%